Geschichte der Arabischen Litteratur in 1898 and 1902. - Brockelmann, Carl, 1868-1956. (Leiden Leiden Leiden Leiden)
6 c. (1. c. xxiii, 593 s. ; 2. c. xiv, 624 s. ; ek 1 xviii, 1029 s. ; ek 2 xix, 1057 ; ek 3,1 xx, 758 s. ; ek 3,2 ix, 614 s.)